1987
DOI: 10.2190/7m4a-w0g1-4dfy-kfet
|View full text |Cite
|
Sign up to set email alerts
|

Three Forms of Instruction

Abstract: With the rate of emergence and complexity of new knowledge and technology, formal instruction has become endemic to organizational life. One result is a series of challenges to the traditional instructional model which is based upon public school practices. Three forms of instruction can be identified lying along the dimensions of density of content and style of personal interaction. The First Form is designed for persons on an entrance level. The goal is the attainment of a minimum of basic skills and appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Appropriate feedback to learners in learning process is a crucial part of education since it can facilitate learning. In online learning, feedback is provided in the synchronic and asynchronic formats (Kowitz and Smith, 1987). Because of the differences between this kind of learning and traditional classroom including the physical separation of the teacher and learners, special kinds of feedback are applicable (Keegan, 1990).…”
Section: Statement Of the Problemsmentioning
confidence: 99%
“…Appropriate feedback to learners in learning process is a crucial part of education since it can facilitate learning. In online learning, feedback is provided in the synchronic and asynchronic formats (Kowitz and Smith, 1987). Because of the differences between this kind of learning and traditional classroom including the physical separation of the teacher and learners, special kinds of feedback are applicable (Keegan, 1990).…”
Section: Statement Of the Problemsmentioning
confidence: 99%
“…Research has shown that instructor feedback helps students to validate their understanding of concepts and theories during the learning process (Bruner, 1962). It is communication between a learner and an instructor referencing an instructional question, which enhances learning (Kowitz & Smith, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Educators use discussion board forums in addition to other forms of communication technology to help students gain a greater understanding of course content while encouraging peer-to-peer (p2p) education. By purposefully creating environments for p2p "creation of knowledge", educators are encouraging what Kowitz and Smith (1987) "defined as the third and most advanced form of instruction" (Moore, 1993, p. 33). Through the utilization of ever increasing technological advancements healthcare educators are able to communicate with students from across the world in real time virtual classrooms which can simulate real world environments.…”
Section: Transactional Distancementioning
confidence: 99%
“…Instructors can also create real-time student-to-student interactions through the use of small group projects which can help to create shared meanings and the creation of new knowledge (Kowitz & Smith, 1987). Further, interactions between course content and students can be emphasized in the traditional F2F classroom quickly through the use of application, Q/A and case study sessions.…”
Section: Intentional Interactionmentioning
confidence: 99%